Dadih, traditional fermented buffalo milk: a comprehensive review of the aspects of gastronomy, health benefits, and product development - Angga Pramana; Bara Yudhistira; Maghfirah Jayalaksamana; Dihan Kurnia; Naila Husnayain; Rianita Pramitasari (Journal of Ethnic Foods)
Abstract Indonesia is a country with a rich array of traditional meals renowned for their health benefits and potential to serve as functional foods, including dadih. Several studies have shown that dadih is a traditional fermented product from Indonesia, with various culinary applications. In addition, it is typically produced from fermented buffalo milk, which forms an unchanged or broken lump when fermented at room temperature. This product is also widely consumed by the Minangkabau ethnic group in Central Sumatra (nowadays known as the provinces of West Sumatra, Riau, Kepulauan Riau, and Jambi), holding a significant position in their culinary practices. Dadih is often traditionally processed through spontaneous fermentation in bamboo containers without the need for additional inoculation with buffalo milk. The indigenous dadih lactic acid bacteria has been evaluated to have several advantages, including immunomodulatory, antioxidant, antimutagenic, hypocholesterolemic, and antimicrobial properties, by various mechanisms. In addition, this product offers significant nutritional content, promoting digestive health and enhancing the body’s resilience.